Written Law and Interpretation, According to Gény - Velásquez Villamar, Gastón Alexander (Universidad Hemisferios, 2021)
The objective of this article is to understand the relationship between written law and the interpretation of the terms proposed by FranÃ§ois Gény, taking into account his description of the interpretive phenomenon and the elements of its rationality. This paper is strictly referred to his work titled